How do online bookstores influence the sales of traditional bookstores in China? - Kuhlmann, J.; Xu, P.; Li, S.; Zhou, L. (Pacific Asia Conference on Information Systems Proceedings, 2016)
Bookstores have been strongly affected by the rise of electronic commerce. Traditional (physical) bookstores now have to compete with online counterparts that possess several advantages over them, such as lower prices and 24/7 availability. This paper investigates the influence that online bookstores have on the sales of physical bookstores in China. The geographic restriction is based on the particularities of the Chinese market that differentiate China from other markets, both in the book market as well as in the adoption of E-commerce. Since there is a lack of overview in the English academic literature on this topic, we conducted a literature review to summarize the current state of research. Our research highlights multiple advantages and disadvantages of physical and online bookstores in the Chinese market, which in turn influence the sales of traditional bookstores. This paper offers a theoretical and a practical contribution. Participants of the Chinese book market can use the results to better assess and improve their market position by addressing the disadvantages or building on the strengths identified during the review. Furthermore, this paper can serve as a starting point for English researchers, as almost no research on this topic has been published in English.